GIS-ASSISTED COASTAL ZONE PLANNING - Hans J.B. Rooseboom (JOURNAL OF COASTAL DEVELOPMENT, 1998)
In this paper we opine that a geographic information system can provide essential and much needed support to integrate coastal and marine resource management, provided, however, that a number of preconditions have been met. Detailed and highly accurate geo-referenced digital data are available to the coastal zone manager. If required, sub meter accuracy can be introduced into the planning process. We would, however, like to propound that the most effective mapping scale for integrated coastal and marine resource management (in Indonesia) is 1:250.000, which would hardly warrant sub-meter accuracy. The necessity to include the motivations and activities of multitude of stakeholders further diminishes the need for detailed and sophisticated systems, as their disorderly, random and often haphazard behavior defies attempts at accurate modeling. We therefore believe that GIS for coastal resource management is best used as a system to monitor events, and to interpret the results there through querying the database by way of algorithmic as well as visual methods and techniques. The resulting information should then be presented as an easily accessible and friendly decision support tool to the coastal zone managers. A GIS, in other world, should be a management support tool, not a device to spout answers (decisions) derived from mathematical calculations performed on a “model” of the marine and coastal zone. By designing the system to monitor events and change at scale of 1:250.000, the managers would be forced to concentrate on the main trends and developments, and see the coastal zone in its relation to its wider surroundings. They would moreover avoid the collection and loading of superfluous details, which generally result in data-overload and system slow-downs, if not failures. And most importantly, a manager would be forced to use his creativity and imagination in guiding, directing and cotrolling the utilization of marine and coastal resources